Heparin-induced Thrombocytopenia in Pregnancy: An Interdisciplinary Challenge: A Case Report and Literature Review. Issue 1 (March 2017) - Mauermann, E.; Vökt, C.; Tsakiris, D.A.; Tobler, D.; Girard, T.
Abstract : ( Int J Obstet Anesth. 2016;26:79–82) Heparin-induced thrombocytopenia (HIT) occurs seldom during pregnancy (<0.1%) but may lead to thrombosis when untreated.